Insights into COVID-19 Delta variant (B.1.617.2) - Angel Yun-Kuan Thye; Ke-Yan Loo; Kyle Bond Chene Tan; Jenny May-Sim Lau; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
Since beginning of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), different variants of concern (VOC) have been discovered. One of the variants that stood out was the Delta variant (B.1.617.2), first found in India. It caught worldwide attention due to its greater transmissibility than the progenitor strain and the first variant of concern (VOC)- Alpha variant (B.1.1.7). B.1.617.2 spread rapidly across the globe and became a VOC due to its high transmissibility, clinical implications, and impact on vaccine efficacy. This review discusses the background and prevalence of B.1.617.2 and its sensitivity to convalescent sera and vaccinated individuals. We will provide an insight into the impact B.1.617.2 has on vaccine efficacy and discuss the level and type of protection an individual could get by being vaccinated. We will also discuss briefly on the COVID-19 vaccine booster doses and whether it is needed.